Risk factors for pelvic lymph node metastasis in cervical cancer: a retrospective analysis of 186 patients - Xingyu Sun; Lijuan He; Shaohua Wang (Frontiers in Oncology)
BackgroundPelvic lymph node metastasis is a critical factor influencing prognosis and treatment strategies in cervical cancer patients. This study aimed to identify significant clinical and pathological risk factors associated with pelvic lymph node metastasis in patients with cervical cancer.MethodsWe conducted a retrospective analysis of 186 cervical cancer patients treated at the Affiliated Hospital, Southwest Medical University from January 2010 to December 2020. Patients were divided into two groups: those with pelvic lymph node metastasis (n=40) and those without (n=146). Data on demographics, clinical characteristics, pathological features, and treatment modalities were collected. Statistical analysis included t-tests, chi-square tests, and logistic regression to evaluate potential risk factors for lymph node metastasis.ResultsPatients with pelvic lymph node metastasis were significantly older (mean age 52.5 ± 8.3 years) than those without metastasis (mean age 48.7 ± 10.2 years; p=0.023). High-risk HPV positivity was significantly associated with lymph node metastasis (75% vs. 41%, p=0.001). Lymphovascular invasion was observed in 75% of the metastatic group compared to 24.7% in the non-metastatic group (p<0.001). Tumor size >4 cm was more frequent in patients with metastasis (50% vs. 12.3%, p<0.001). Multivariate logistic regression analysis identified high-risk HPV infection (OR 4.13, 95% CI: 2.09-8.17, p<0.001), lymphovascular invasion (OR 7.87, 95% CI: 4.05-15.29, p<0.001), and tumor size >4 cm (OR 6.24, 95% CI: 3.24-12.02, p<0.001) as independent risk factors for pelvic lymph node metastasis.ConclusionThis study identifies several independent risk factors for pelvic lymph node metastasis in cervical cancer, including high-risk HPV infection, lymphovascular invasion, and tumor size greater than 4 cm. These findings can help guide clinical decision-making and individualized treatment planning, improving outcomes for patients with cervical cancer. Further prospective studies are warranted to validate these findings.